PEMBUATAN WEDDING DRESS MENGGUNAKAN BAHAN SONGKET DAN VARIASI KAIN TILE PADA MATA PELAJARAN PEMBUATAN BUSANA CUSTOM MADE - Ernita Sari, Intan; Ridwan Misbahudin, Agus (Jurnal Socia Akademika, 2025)
This study aims to develop and implement a custom-made wedding dress design that combines songket fabric as the main element with tile fabric variations to support the aesthetics. This project was conducted within the scope of learning the subject of custom-made dressmaking at SMK Sultan Agung Ngawen, Blora, using a qualitative descriptive approach based on project-based learning (PBL). Songket fabric was chosen for its rich motifs and cultural value, while tile fabric was incorporated to create a light, elegant, and modern feel. The production process includes design, material selection, pattern making, sewing, and final finishing, all of which are carried out by the students of Class XI. Data was collected through direct observation, interviews, documentation, and evaluation of students' competencies in terms of knowledge and skills. The results of the study show that integrating traditional and modern materials not only improves the visual quality and selling value of products but also fosters students' appreciation for local textile heritage. Additionally, this activity fosters the development of technical skills, design creativity, and student readiness to meet the challenges of the culture-based fashion industry. This study makes an important contribution to the development of innovative and contextual project-based vocational learning.